KARAKTERISTIK BUTIR SOAL TRY OUT UJIAN NASIONAL SMA MATA PELAJARAN MATEMATIKA Se-KOTA MATARAM DENGAN MENGGUNAKAN PROGRAM ITEMAN - Habib Ratu Perwira Negara; Kiki Riska Ayu Kurniawati (Jurnal Varian, 2018)
The purpose of this research was to know how characteristic items of Try Out National Exam Year 2010/2011 at Senior High School on Mathematics Subject in Mataram City that analyzed by using Iteman Program. The characteristic in question was whether the item can be used or not based on the difficulty level of the item, the difference in power, and the functioning of the answer option. The research method used was descriptive. Techniques of collecting data in the form of documents. Source of data in the form of answer sheet of computer package 61 of Try Out National Exam Year 2010/2011 at Senior High School on Mathematics Subject in Mataram City. Aspects analyzed by using this Iteman Program include the level of difficulty item, different power, and the function of whether or not the answer choice. Based on the results of Item of Analysis Try Out National Examination of School Year 2010/2011 Senior High School on Mathematics Subjects in Mataram City by using Iteman Program, it can be concluded that for the level of difficulty Package 61 was classified. Different power for package 61 has a good category. For the reliability of having a high category and a matter of Try Out Package 61 there are 23 problems received with the improvement of 4, 5, 8, 9, 14, 16, 17, 18, 19, 20, 21, 22, 23, 24, 26, 28, 30, 31, 32, 34, 35, 36, and 40. Improvements need to be made on the less functioning effluent. There are 15 accepted questions: 1, 2, 3, 7, 10, 11, 12, 13, 15, 27, 29, 33, 37, 38, and 39. And there are 2 rejected questions 6 and 25.